Passeggiando per la Federico II - Alessandro Castagnaro (Fuori Collana, 2019)
This volume - has the prevailing goal of let be known the effect and importance of the different locations of the University Federico II in the extended urban context of the metropolitan area of ​​Naples. A publication in the occasion of Federico II's birthday, 795 years of history that fall on 7 June 2019. The twenty-seven sites of the University Federico II, gathered in this volume and described by my colleagues of the Department of history of Architecture of our University, are strongly linked to the history of the city, from the early Middle Ages to the modern and contemporary age. In fact, through their description, come to light events linked to civil, political and art history with the evolution of the style and the different artistic forms. The aim of the publication is to make people capable to understand the significant role of the locations of the Federico II, in the context of the metropolitan city, and how these valuable Architectures, plenty of art, thanks to the University are preserved, given value, repurposed, and offered in usage of a large audience.